Rancang Bangun Sistem Informasi dan Prediksi Penjualan Jamu menggunakan Metode Fuzzy Time Series - Rohman, Abdur; Sucipto, Hadi; Heru Mujianto, Ahmad (Inovate, 2023)
Information systems and sales predictions for herbal herbal medicine are needed to see sales developments in the form of graphs and tables, while predictions are used to see sales predictions in the next 3 days, 7 days ahead, 14 days ahead and 1 month ahead. The function besides seeing sales predictions is also used for future stock planning. The prediction method used is fuzzy time series cheng by utilizing sales data in the past with the first stages of collecting actual data, determining the width of the interval and the number of intervals, defining fuzzy sets, fuzzification, making tables of Fuzzy Logic Relations and Fuzzy Logic Relations Group and the last defuzzification. For the accuracy of the prediction results using the MAPE formula where in this study for 3 days prediction the MAPE value was 13.31% while for 7 days it was 7.25%, for 14 days it was 10.53% while for 1 month it was 6 ,64%. The result of this research is an information system which contains sales charts, sales tables, stock information and sales predictions Keywords: Herbal Medicine, Sales Prediction, Fuzzy Time Series